Symbiotic Relationship between Capital Budgeting and Financing Decision-Making - Sari, Ratna; Muslim, Muslim (The Journal of Business and Management Research, 2024)
This study aims to explore the symbiotic relationship between capital budgeting and financing decision-making in corporate financial management. The research design and methodology involve a comprehensive literature analysis, incorporating seminal theories and recent empirical studies to elucidate the interconnectedness of investment choices and funding strategies. Findings indicate that effective coordination between capital budgeting and financing decisions is essential for firms to optimize resource allocation, manage financial risks, and enhance shareholder value. Strategic capital allocation enables firms to prioritize investments that offer the highest potential for value creation while aligning investment decisions with financing considerations, which ensures efficient use of financial resources. The implications of this research suggest that integrating capital budgeting and financing decision-making enables firms to navigate dynamic market conditions, adapt to regulatory changes, and capitalize on emerging opportunities. By addressing these research gaps, scholars can better understand the factors driving firms' strategic planning and value-creation initiatives.